2017
DOI: 10.1093/eep/dvx016
|View full text |Cite
|
Sign up to set email alerts
|

Generational comparisons (F1 versus F3) of vinclozolin induced epigenetic transgenerational inheritance of sperm differential DNA methylation regions (epimutations) using MeDIP-Seq

Abstract: Environmentally induced epigenetic transgenerational inheritance of disease and phenotypic variation has been shown to involve DNA methylation alterations in the germline (e.g. sperm). These differential DNA methylation regions (DMRs) are termed epimutations and in part transmit the transgenerational phenotypes. The agricultural fungicide vinclozolin exposure of a gestating female rat has previously been shown to promote transgenerational disease and epimutations in F3 generation (great-grand-offspring) animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 66 publications
2
48
0
Order By: Relevance
“…For high-dose VIN, epimutations were observed in the male F3 germline [12] and sperm [19]. To our knowledge a single report evaluated genome wide epimutations in F1 and F3 sperm due to VIN exposure [21]. Using methylated DNA immunoprecipitation followed by hybridization to a promoter microarray (MeDIP-Chip), Beck et al found that the F1 generation had fewer differentially methylated promoter regions compared to the ancestrally exposed F3 generation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For high-dose VIN, epimutations were observed in the male F3 germline [12] and sperm [19]. To our knowledge a single report evaluated genome wide epimutations in F1 and F3 sperm due to VIN exposure [21]. Using methylated DNA immunoprecipitation followed by hybridization to a promoter microarray (MeDIP-Chip), Beck et al found that the F1 generation had fewer differentially methylated promoter regions compared to the ancestrally exposed F3 generation.…”
Section: Discussionmentioning
confidence: 99%
“…This was repeated in the F2 generation, resulting in F3 males that derived from paternal transmission of the germline. Second, we injected a much lower and realistic dosage (1 mg/kg) of VIN exposure than previous reports (50-100 mg/kg, e.g., [21]). Third, we compared outcomes of VIN, an antiandrogenic fungicide, with those of A1221, a weakly estrogenic PCB mix, to determine whether different classes of EDCs have similar or different effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the mechanism is unclear, this non-conventional inheritance likely occurs independent of DNA base-sequence and involves the inheritance of an epigenetic factor(s) via the germline 6,7 . Candidates in mammals include: DNA methylation, histone modifications, and/or non-coding RNA 1,2,4,[8][9][10] . How an epigenetic message resists reprogramming and is transmitted between generations remains elusive.…”
Section: Main Textmentioning
confidence: 99%
“…Few mammalian models of TEI exist and the majority focus on paternal inheritance 1,2,[8][9][10][11] .…”
Section: Main Textmentioning
confidence: 99%